Anatomy Touch Table Project - Russell, Roger; Barber, Marlena (My University, 2018)
Objectives : The library has seen great usage in its anatomical model collection but struggles to meet patron demand during peak times. The objective of this project was to improve patron experience and utilization of anatomical resources, to better anticipate and understand period of high patron demand for anatomical models, and to ensure maximum user availability of models. Methods : Usage statistics were analyzed on anatomical models and web-based anatomical model resources. Anecdotal data from librarian and staff interaction with library patrons was also recorded. The library launched several new approaches to achieve the objective including purchasing a large Touch Table on which electronic anatomy resources can be used, working directly with faculty and students to better anticipate and understand periods of high demand, and ordering additional models. Results : Successes have been increased use of the physical anatomical model collection and increase in the types of students who are using the collection. Challenges have been convincing students or teaching faculty to use the electronic anatomy resources on the Touch Table, despite sponsoring classes, working with the university’s tutoring center, and trying various locations. Other challenges have been making the anatomical model collection available “just in time” during periods of high demand. A reservation system was piloted but quickly abandoned due to unanticipated problems using text messaging for alerts that a model was ready for use. Conclusion : Anatomical models resources are in demand on most health sciences campuses. Physical anatomical models are still most preferred, even when good and more accessible electronic versions are made available. Transitioning from physical to electronic for anatomical model resources will require partnership and buy-in from teaching faculty resulting in gradual culture change.
Keywords: anatomical models; technology; touch table; access services; user services